Federated States of Micronesia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Federated States of Micronesia. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the Micronesian economy continued its gradual recovery in fiscal year 2016 (ending September 30), after three years of contraction during 2012-14. Real GDP is estimated to have grown by 3.0 percent in 2016, driven by increased construction activity related to infrastructure projects. Consumer prices remained broadly stable. The fiscal balance recorded an estimated surplus of 9 percent of GDP, after another year of strong revenues from fishing license fees. In 2017, growth is expected to moderate to 2 percent, as the recovery continues at a slower pace. Despite the recovery, risks are tilted to the downside beyond the near term.